A 16-Year Study on Incidence and Progression of Diseased Sphenoethmoidal (Onodi) Cell. (5th June 2020) - Huang, Ethan I.; Kuo, Chia-Ling; Lee, Li-Wen
Abstract : Traumatic operative injury of the optic nerve in an endoscopic sinus surgery may cause immediate or delayed blindness. It should be cautioned when operating in a sphenoethmoidal cell, or known as Onodi cell, with contact or bulge of the optic canal. It remains unclear how frequent progression to visual loss occurs and how long it progresses to visual loss because of a diseased sphenoethmoidal cell. Research to discuss these questions is expected to help decision making to treat diseased sphenoethmoidal cells. From July 2001 to June 2017, 216 patients received conservative endoscopic sinus surgery without opening a diseased sphenoethmoidal cell. We used their computed tomography images of paranasal sinuses to identify diseased sphenoethmoidal cells that could be associated with progression to visual loss. Among the 216 patients, 52.3% had at least one sphenoethmoidal cell, and 14.8% developed at least one diseased sphenoethmoidal cell. One patient developed acute visual loss 4412 days after the first computed tomography. Our results show that over half of the patients have a sphenoethmoidal cell but suggest a rare incidence of a diseased sphenoethmoidal cell progressing to visual loss during the follow-up period.